Pod Dehiscence in Hairy Vetch (Vicia villosa Roth) - Kissing Kucek, Lisa; Riday, Heathcliffe; Rufener, Bryce P.; Burke, Allen N.; Eagen, Sarah Seehaver; Ehlke, Nancy; Krogman, Sarah; Mirsky, Steven B.; Reberg-Horton, Chris; Ryan, Matthew R.; Wayman, Sandra; Wiering, Nick P. (Frontiers in Plant Science, 2020)
Hairy vetch, Vicia villosa (Roth), is a cover crop that does not exhibit a typical domestication syndrome. Pod dehiscence reduces seed yield and creates weed problems for subsequent crops. De novo domestication efforts aim to reduce pod dehiscence in hairy vetch. To characterize pod dehiscence in the species, we quantified visual dehiscence and force required to cause dehiscence among 606 genotypes grown among seven environments of the United States. To identify potential secondary selection traits, we correlated pod dehiscence with various morphological pod characteristics and field measurements. Genotypes of hairy vetch exhibited wide variation in pod dehiscence, from completely indehiscent to completely dehiscent ratings. Mean force to dehiscence also varied widely, from 0.279 to 8.97 N among genotypes. No morphological traits were consistently correlated with pod dehiscence among environments where plants were grown. Results indicated that visual ratings of dehiscence would efficiently screen against genotypes with high pod dehiscence early in the de novo domestication process. Force to dehiscence may be necessary to identify the indehiscent genotypes during advanced stages of selection.